Teacher’s Strategies in Increasing Students’ Motivation in Learning English - Saputra, Triyono; Regina, Regina; Riyanti, Dwi (Universitas Pahlawan Tuanku Tambusai, 2023)
This research was conducted to analyze strategies used by the teacher in increasing the motivation of 11th grade students in learning English and factors influence that strategies. This research is for English teacher and 11th grade students of SMK PGRI Pontianak. The data were collected using interview with teacher and questionnaires for students. Data analyzed using familiarization and organization, coding and reduction, interpretation and representation. Strategies for teaching listening skills using audio and exercise. Second strategy for teaching speaking skills is reading aloud the text. The third strategy for teaching reading skills is read together, then student read each paragraph. The last is use mind mapping. There are some factors that influence the strategy. Factor of listening and speaking strategies is the low and limited understanding of students. For reading strategy, the lack of student focus. The last factor in writing, students are less able to develop their writing.